Developing of applications on the Googles Android powered devices and arduino-powered platforms 2 - Wee, Teck Hian (2015)
Mobile devices have taken root in our current society and is here to stay for every long time. Besides being a mode of communication, it is also seen as a portable source of entertainment or an alternative form of service provider such as I-banking, remote controller & etc. It is evolving at a remarkable rate integrating different modes of services together into a single device. Adruino is a type of microcontroller that is capable of interacting with the outside environment through the use of sensors to collect data. Many innovative applications were built around it due to its cost and flexibility, making it a top choice among developers. Interaction between various devices across platforms is a common occurrence in our modern era and security is the up and coming priority in applications due to this trend. Secure communication between devices is of high importance due to classified nature of information transferred or even dire consequences of miscommunication in the case of critical automated services such as nuclear plants. This project aims to create an application that allows secured and error-free transmission of firmware data to be transferred over-the-air from an Android-based mobile device to an Adruino-based sensor equipment that is mounted in a real world operational environment. Two factor authentication protocol is used to ensure the authenticity of the device initiating transfer and an acknowledgement factor is put in place for the Over-The-Air transfer protocol to ensure the correctness and integrity of the firmware data packets. XBee device is being used as the communication medium between Android-based devices and Adruino-based device. The transfer protocol between the mentioned devices through XBee had been established and the application will be built on this foundation. The successful implementation of this application allows users to be authenticated by the Adruino-based device before proceeding with the transfer of firmware data. However, there are still unexplored possibilities for the improvements of this protocol and innovative features & functions yet to be added, leaving room for future growth of this application.